Effect of Diabetes Exercise on Reduction of Blood Glucose Levels in Patients with Type II Diabetes Mellitus - Sari, Intan (Faculty of Medicine, Universitas Tadulako, 2025)
Background: The rising prevalence of diabetes mellitus in Indonesia from 10.9% in 2018 to 11.7% in 2023, positioning the country fifth globally with 19.47 million cases highlights an urgent public health concern requiring effective management strategies. Objective: To determine the effect of diabetes exercise on blood glucose levels (BGLs) in patients with type 2 diabetes mellitus. Methods: This pre-experimental study used a one-group pretest-posttest design involving 18 respondents who performed diabetes exercise three times per week for four weeks, each session lasting 30 minutes. Results: Data were analyzed using frequency distribution, the Shapiro-Wilk test, and the Wilcoxon Signed Rank Test. Normality tests showed significance values of 0.521 (pre-test) and 0.946 (post-test), indicating normally distributed data. The Wilcoxon test yielded a p-value of 0.001 (<0.05) with a large effect size (0.68), demonstrating a significant reduction in BGLs after the intervention. Mean BGLs decreased substantially from pre- to post-exercise, suggesting improved glycemic control. These findings confirm that regular diabetes exercise enhances insulin sensitivity and promotes better glucose utilization through increased muscle activity. Conclusion: Diabetes exercise significantly reduces blood glucose levels in patients with type 2 diabetes mellitus and should be recommended as a complementary, non-pharmacological therapy for optimal glycemic management.